Islam and the Charismatic Revolutionary Social Transformation of Iran - Acuff, Jonathan (Totalitarian movements and political religions, 2003)
Contemporary explanations of revolution privilege material power and the interests of 'rational' actors over ideas. Drawing on Max Weber's seminal insights and recent work by social constructivists, I argue that agents and ideas were important in both the revolutionary situation and outcome of the Iranian Revolution. The revolutionary outcome in particular was the result of the combination of the charismatic leadership of Ayatollah Khomeini, the 'agent', with the normative content of political Islam, the 'structure'. Given the relative explanatory power of this method, the emergence of a 'fourth school' in the literature on revolutions is warranted.